Impact of heat stress on Mytilus edulis: contaminants affect survival and HSP 70 proteoform expression - R. Péden; J. Letendre; B. Rocher; F. Durand; F. Le Foll; P. Chan; D. Vaudry; F. Bultelle (MDPI AG, 2014)
Not available